Effect of moderately intense perioperative glucose control on renal allograft function: a pilot randomized controlled trial in renal transplantation. Issue 10 (24th September 2016) - Parekh, Justin; Roll, Garrett R.; Wisel, Steven; Rushakoff, Robert J.; Hirose, Ryutaro
Abstract: Recipient diabetes accounts for 34% of end‐stage renal disease in patients awaiting renal transplantation and has been linked to poor graft function. We conducted a single‐center, open‐label, randomized controlled trial to determine whether moderately intense glucose control during allograft reperfusion would reduce the incidence of poor graft function. Adult diabetics undergoing deceased donor renal transplant were randomized to moderately intense glucose control (n=30) or standard control (n=30). The primary outcome was poor graft function (dialysis within seven days of transplant or failure of serum creatinine to fall by 10% for three consecutive days). Recipients with moderately intense glucose control had less poor graft function in the intention‐to‐treat (43.3% vs 73.3%, P =.02) and per‐protocol analysis (43.2% vs 81%, P <.01). Recipients with moderately intense control also had higher glomerular filtration rate (GFR) at 30 days after transplant in the per‐protocol and intention‐to‐treat analyses. There were no episodes of severe hypoglycemia in either group and no differences in mortality, seizures, stroke, graft loss, or biopsy‐proven rejection. Moderately intense glucose control at the time of allograft reperfusion reduces the incidence of poor graft function in diabetic renal transplant recipients and improves glomerular filtration rate at 30 days.